2003
DOI: 10.1001/archpsyc.60.7.709
|View full text |Cite
|
Sign up to set email alerts
|

Prior Juvenile Diagnoses in Adults With Mental Disorder

Abstract: Most adult disorders should be reframed as extensions of juvenile disorders. In particular, juvenile conduct disorder is a priority prevention target for reducing psychiatric disorder in the adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
617
2
16

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,757 publications
(669 citation statements)
references
References 80 publications
(98 reference statements)
34
617
2
16
Order By: Relevance
“…But this result has not been replicated. Investigating the prior juvenile diagnoses in adults with mental disorder among the Dunedin prospective-longitudinal cohort, Kim-Cohen et al [34] reported that young adult mania diagnosed before 26 years of age was likely to be preceded by conduct and/or oppositional disorder and juvenile depression but not by ADHD.…”
Section: Discussion J Limitations and Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…But this result has not been replicated. Investigating the prior juvenile diagnoses in adults with mental disorder among the Dunedin prospective-longitudinal cohort, Kim-Cohen et al [34] reported that young adult mania diagnosed before 26 years of age was likely to be preceded by conduct and/or oppositional disorder and juvenile depression but not by ADHD.…”
Section: Discussion J Limitations and Strengthsmentioning
confidence: 99%
“…Despite the fact that diagnosing BD during adolescence remains difficult [7,8] and that controversies still remain concerning the existence of BD-NOS and BD-II in this age population, mainly in Europe [44], typical BD-I in teens is no longer controversial [11]. In adolescents, BD is a frequent diagnosis but BD-I is much more rare with lifetime prevalence rates of 1 and 0.1%, respectively [39,34].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, interventions increasing awareness about school bullying, specifying rules and social norms against bullying, and providing support and protection for children who are bullied (social worker support, mentoring) have proved successful and should be generalized [67,68,72,89].…”
Section: Clinical and Policy Implicationsmentioning
confidence: 99%
“…(Kim-Cohen et al 2003;Collishaw et al 2004;MacDiarmid et al, forthcoming;Whear et al 2013) Epidemiological surveys that span many countries and over 50 years estimate the prevalence of psychiatric disorders among school-age children to lie between 3-22% (Canino et al 1995;Offord 1995;Roberts, Attkisson, and Rosenblatt 1998;Costello, Egger, and Angold 2005). The British Child and Adolescent Mental Health Surveys in 1999 and 2004 (Meltzer et al 2000;Green et al 2005) both reported the prevalence of psychiatric disorder to be approximately 10% among school-age children and imply that two to three children in an average class of 20-30 will be significantly impaired as a result of their poor mental health.…”
Section: Editorial Emotional and Behavioural Difficulties And Mental mentioning
confidence: 99%